Visualization of harassment in university tendederos; a construction of linguistic landscapes - Chan Pech, Cándido (2021)
University spaces are scenarios where gender violence and sexual harassment live in everyday life, they have rarely been exhibited by the domination of the power of the patriarchal system in addition to the threat of coercion accordingly. However, the collective need to visualize it in the so-called     clotheslines, where the students writeon sheets of paper their anonymous complaint; are practices that are visualizing  and  exhibiting the representations of  sexual harassment:  looksand propositions.   From a semiotic-linguistic treatment, the invitation to elucidate the meaning of such a practice as a collective setting of visualizing the inappparent of violence in the university was heeded. The main intention of this article is to propose the  clothesline  as the construction of a linguistic landscape and as a practice of visualization of sexual harassment as an immediate reference of the conceptualizations in the spaces of the university.